Pengaruh Cinta Uang, Literasi Keuangan, dan Sikap Keuangan terhadap Manajemen Keuangan Pribadi pada Generasi Z : (Survei pada Mahasiswa/i Komunitas GenBI Sumatera Selatan) - Intan Nurjanah; Hilda Hilda; Lidia Desiana (Jurnal Bisnis Inovatif dan Digital, 2025)
The accelerated progress in technology alongside the global integration of digital trends have significantly shaped the financial behavior of Generation Z. This demographic often displays short-term financial tendencies, such as impulsive spending, the adoption of the “You Only Live Once” (YOLO) mindset, and doom spending, which often undermines long-term financial planning. This study seeks to examine the extent to which love of money, financial literacy, and financial attitude influence personal financial management among members of GenBI South Sumatra. Information was obtained via surveys distributed to 63 participants, proportionally selected from a total population of 175 students from UIN Raden Fatah, Sriwijaya University, and Sriwijaya State Polytechnic. The study employed a quantitative research design using Structural Equation Modeling (SEM) method with the SmartPLS 3.2.9 software. The data reveal that love of money, financial literacy, and financial attitude each have a positive and statistically significant impact on the personal financial management of Generation Z.